Connection between geotectonic zoning of territory and its oil and gas potential (on the example of Dniper-Donets rift) - Yesypovych, Stanislav; Titarenko, Olga; Bondarenko, Alla; Bubniak, Andrii (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2018)
Connection between geotectonic zoning of the territory and its oil and gas potential is shown on example of the actual drilling data of Dnieper-Donets Rift. First of all, the zones of connection of different geotectonic elements are the most promising, which is confirmed by their modern geodynamic activity. In this article, such transition zones are called seam rift zones (SRZ) for combining compression (seam) and stretching (rift) conditions. SRZs are distinguished by a wide range of aerospace, morphometric, geological and geophysical data.